137k views
2 votes
(3b^3-4b^1-7)(2b^2-b^1-9)

*Multiplying Polynomials *

User Olafant
by
5.7k points

1 Answer

4 votes

Answer:


6b^(5)-3b^(4)-35b^(3)-10b^(2)+43b+63

Explanation:

we have to find the multiplication of following polynomials

As we know that the multiplication of two polynomials are done in following way

let we have two polynomial (ax+b) and (cx+d) their product would be

(ax+b)(cx+d)

=ax(cx+d)+b(cx+d)

=acx² + axd + bcx + bd

Now similarly for the given polynomial we have


(3b^(3)-4b-7)*(2b^(2)-b-9)

it could be written as

=3b³(2b²-b-9) -4b(2b²-b-9) -7(2b²-b-9)

Multiplying inside with values

=
6b^(5)-3b^(4)-27b^(3)-8b^(3)+4b^(2)+36b-14b^(2)+7b+63

Combining same values

=
6b^(5)-3b^(4)-27b^(3)-8b^(3)+4b^(2)-14b^(2)+36b+7b+63

=
6b^(5)-3b^(4)-35b^(3)-10b^(2)+43b+63


User Peleyal
by
5.4k points